2019
DOI: 10.12669/pjms.35.6.976
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Hemoglobinopathies: A potential threat to the premarital screening program

Abstract: Objectives:To evaluate the prevalence of undiagnosed hemoglobinopathies among individuals visiting the premarital screening Centre.Methods:This study was conducted at Premarital Screening Centre, King Fahad Central Hospital and Research Centre, Jazan, between January 2018 and October 2018. A total of 3,970 (male n =1,859 and female n = 2,111) individuals were included in the study. Data of complete blood count, hemoglobin electrophoresis and sickling tests of all individuals recruited in the study were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…22,23 It should also be kept in mind that alpha and beta thalassemia are prevalent in this area. 24,25 As Hb electrophoresis was not carried out in this study, the authors could not make a definitive diagnosis of the thalassemia trait.…”
Section: Discussionmentioning
confidence: 93%
“…22,23 It should also be kept in mind that alpha and beta thalassemia are prevalent in this area. 24,25 As Hb electrophoresis was not carried out in this study, the authors could not make a definitive diagnosis of the thalassemia trait.…”
Section: Discussionmentioning
confidence: 93%
“… 12 Additionally, in a study assessing the prevalence of haemoglobin abnormalities among attendees of a single premarital screening centre in the Jazan region between January and October 2018, it was reported that among 3790 screened individuals, 1312 (28.5%) were identified as having hemoglobinopathies. 13 However, studies assessing the factors associated with the rejection of premarital clinical counselling in the Jazan region, in the south of Saudi Arabia, are currently lacking. This study aims to fill this gap of knowledge concerning a region with high prevalence of inherited blood disorders in comparison to other regions in the kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…There are two copies of αglobin gene (α2α1) on chromosome 16, therefore each diploid individual carries four copies of αglobin gene (α2α1/α2α1). Most non-deletion αthalassemia mutations involved only one single αglobin gene, and these αglobin mutations generally do not have clinical consequences which can be regarded as silent thalassemia, as the other three normal αglobin genes can compensate for the mutation (Hamali & Saboor, 2019). Usually, non-deletion αthalassemia heterozygous are silent carriers with normal hematological profiles, except for few mutations such as αα CS (HBA2:c.427T>C) (He et al, 2017).…”
Section: Discussionmentioning
confidence: 99%